Study of the behaviour of the azeotropic mixture ethanol-water with different ionic liquids - Elena Gomes (2009)
In this work, experimental data of isobaric vapour-liquid equilibria for the ternary system ethanol + water + 1-hexyl-3-methylin-iidazolium chloride ([C(6)mim][Cl]) and forthe corresponding binary systems containing the ionic liquid (ethanol + [C(6)mim][Cl], water+ [C(6)mim][Cl]) were carried out at 101.300 kPa. VLE experimental data of binary and ternary systems were correlated using the NRTL equation. In a previous work [N. Calvar, B. Gonzalez, E. Gomez, A. Dominguez, J. Chem. Eng. Data 51 (2006) 2178-2181], the VLE of the ternary system ethanol + water + [C(4)mim][Cl] was determined and correlated, so we can study the influence of different ionic liquids in the behaviour of the azeotropic mixture ethanol-water.